An Empirical Analysis of Macroeconomic and Bank Specific Factors Ascertaining Bank Deposit: A Study on Bangladesh - Farhana Nasrin (International Journal of Economics and Financial Issues, 2023)
Bank working capital is largely determined by the level of bank deposits. As the primary source of funds for carrying out lending activities, deposits are the lifeblood of a banking firm. More savings encourages more investment which in turn ensures economic growth. This paper tries to find out relevant factors influencing volume of deposit mobilization by commercial banks. The study is based on the opinion of 200 sample professionals from 29 listed private commercial banks in Bangladesh. The result shows that Government monetary policy, bank size, diversified services, state of local and national economy dominates the collection of bank deposit by commercial banks. Probable implication from the findings is investment friendly government monetary policy that can lead towards improving bank-specific factors as enhancing bank size and ensuring diversified services for more deposit attraction.